Rancang Bangun Sistem Pengaturan Kecepatan Otomatis Jumlah Tetesan Infus Pada Pasien Berdasarkan Uji Linieritas - Mohammad Sezar Nusti Ilhami; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The development of medical science and increasingly sophisticated technology has led to demands for convenience. Errors in giving intravenous fluids can be bad for patients. Currently the regulatory system carried out by medical personnel to regulate each drip infusion in patients is still done manually, this condition will certainly require the attention of a nurse or nurse seriously because the possibility of an error will be large. The nurse also must constantly monitor the drip drip whether it is still stable or not. Sometimes the condition of the infusion is not in accordance with the specified dose even though the administration of an inappropriate infusion dose can cause negative effects on the patient. An intensive care unit recently found 47% of side effects were due to medication and wrong dosage. Based on these problems, we need an Automatic Speed ​​Management System for Number of Infusion Droplets in Patients Based on Linearity Tests that can help nurses to monitor the condition of the infusion drops whether it is still the same as the dose set or has changed. In this system, several components are used: the NodeMCU microcontroller to process data and perform Linear Equation calculations, a photodiode sensor that is useful for detecting whether droplets are present or not, stepper motors as movers and regulators for infusion droplets. resulting from the linear equation is linear or not when applied in the system.